2021
DOI: 10.1182/hematology.2021000261
|View full text |Cite
|
Sign up to set email alerts
|

How immunodeficiency can lead to malignancy

Abstract: Immunodeficiency, whether acquired in the case of human immunodeficiency virus (HIV) infection or congenital due to inborn errors of immunity (IEIs), presents clinically with not only infection and immune dysregulation but also increased risk of malignancy. The range of malignancies seen is relatively limited and attributable to the particular cellular and molecular defects in each disease. CD4+ T-cell lymphopenia in people living with HIV infection (PLWH) and certain IEIs drive the predisposition to aggressiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…As widely described for HIV infection, T lymphopenia or reduced natural killer cells, as well as their dysfunction, may predispose to poor surveillance against neoplastic cells. T-cell dysfunction can also lead to B-cell hyperproliferation and overactivation resulting in a higher risk of developing lymphomas ( 38 , 39 ). In fact, cases of B lymphoma in patients with 22q11.2DS and severe T-cell impairment have been reported in the literature in the past ( 40 , 41 ).…”
Section: Discussionmentioning
confidence: 99%
“…As widely described for HIV infection, T lymphopenia or reduced natural killer cells, as well as their dysfunction, may predispose to poor surveillance against neoplastic cells. T-cell dysfunction can also lead to B-cell hyperproliferation and overactivation resulting in a higher risk of developing lymphomas ( 38 , 39 ). In fact, cases of B lymphoma in patients with 22q11.2DS and severe T-cell impairment have been reported in the literature in the past ( 40 , 41 ).…”
Section: Discussionmentioning
confidence: 99%
“… 108 , 109 , 110 Furthermore, immunodeficiency, whether congenital or acquired, is associated with an increased risk of malignancy. 111 Similarly, the presence of age‐related chronic inflammation and immunosenescence may significantly affect the development of malignancies in frail individuals. 112 In contrast, certain anti‐inflammatory drugs 113 , 114 and immunotherapies 115 ; have been proven to be effective in treating malignancies.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have indicated that chronic inflammation may play a role in the development and progression of cancer 108–110 . Furthermore, immunodeficiency, whether congenital or acquired, is associated with an increased risk of malignancy 111 . Similarly, the presence of age‐related chronic inflammation and immunosenescence may significantly affect the development of malignancies in frail individuals 112 .…”
Section: Discussionmentioning
confidence: 99%
“…It is not yet known whether there is a correlation between lymphocytopenia and poor survival and an association between the specific subset of lymphocytes and inferior prognosis. Previous studies have reported that lymphopenia is an adverse prognostic factor in various solid tumors, Hodgkin's lymphoma (HL), and NHL (24)(25)(26)(27).…”
Section: Discussionmentioning
confidence: 99%